Striato-cortical functional connectivity changes in mild cognitive impairment with Lewy bodies - Novakova, Lubomira; Gajdos, Martin; Barton, Marek; Brabenec, Lubos; Zeleznikova, Zaneta; Moravkova, Ivona; Rektorova, Irena (Parkinsonism & related disorders, 2024)
BACKGROUND: Functional connectivity changes in clinically overt neurodegenerative diseases such as dementia with Lewy bodies have been described, but studies on connectivity changes in the pre-dementia phase are scarce. OBJECTIVES: We concentrated on evaluating striato-cortical functional connectivity differences between patients with Mild Cognitive Impairment with Lewy bodies and healthy controls and on assessing the relation to cognition. METHODS: Altogether, we enrolled 77 participants (47 patients, of which 35 met all the inclusion criteria for the final analysis, and 30 age- and gender-matched healthy controls, of which 28 met all the inclusion criteria for the final analysis) to study the seed-based connectivity of the dorsal, middle, and ventral striatum. We assessed correlations between functional connectivity in the regions of between-group differences and neuropsychological scores of interest (visuospatial and executive domains z-scores). RESULTS: Subjects with Mild Cognitive Impairment with Lewy Bodies, as compared to healthy controls, showed increased connectivity from the dorsal part of the striatum particularly to the bilateral anterior part of the temporal cortex with an association with executive functions. CONCLUSIONS: We were able to capture early abnormal connectivity within cholinergic and noradrenergic pathways that correlated with cognitive functions known to be linked to cholinergic/noradrenergic deficits. The knowledge of specific alterations may improve our understanding of early neural changes in pre-dementia stages and enhance research of disease modifying therapy.
Keywords: kognitivní dysfunkce; Cognition; Cholinergic Agents; Alzheimerova nemoc; kognice; Executive Function; mozek; lidé; Cognitive Dysfunction; exekutivní funkce; Lewy Body Disease; Brain; demence s Lewyho tělísky; Alzheimer Disease; cholinergní látky; Humans